Interest Rate, Savings, and Industrial Performance in Nigeria - Ogunwale Sunday Adeniyi; Odumbaku Abibat Lawal; Mobee Taiwo Ajayi; William Adekunle; Adegboyega S. Oyewole (East Asian Journal of Multidisciplinary Research, 2023)
This study examined the effect of interest rate and savings on industrial productivity in Nigeria. This is imperative because there has been low level of savings and investment amongst other impediment to industrial productivity. The Ordinary Least Square OLS multiple regression analysis was applied on data from Central Bank of Nigeria (CBN) Statistical Bulletin in a model where industrial sector output was the dependent variable while national savings, interest rate INTR and inflation rate INFL were the explanatory variables. The result of the analysis at 5% level of significance shows clearly that savings exerts a significant impact on industrial output in Nigeria. the result also showed that interest rate and inflation rate does not have a significant impact on industrial output in Nigeria. The study concluded that, savings has a significant positive impact on industrial output while the impact of interest rate and inflation rate on industrial output in Nigeria was positive but insignificant. It was recommended that there is a need to bridge the widening gap between lending rate and savings rate to encourage savings to generate needed loanable funds for investment in Nigeria.